PERAN OMBUDSMAN DALAM PENGAWASAN BUMN SEKALIGUS SEBAGAI MEDIATOR BAGI PENCARI KEADILAN NON-LITIGASI UNTUK MENDAPATKAN GANTI RUGI (Studi Kasus di Bandara “X” Yogyakarta) - Fonny Olga Winerungan; Diding Rahmat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2024)
The Society is often in at a disadvantage due to the lack of legal literacy. As a result, when facing legal issues, people are more inclined should be solved through litigation paths, which is throught the court system, rathet than throught non-litigation paths with mediation. As a public service provider, the government through their state-owned enterprises (BUMN) is subject to Standard of Procedure (SOP) violations which cause material and immaterial losses for the society. Citizen should be able file a report or a compensation claim for these violations as regulated in Undang-Undang No.37 Tahun 2008 about Ombudsman and Undang-Undang No.25 Tahun 2009 about Public Service. Not many citizen understand and are brave enough to involve other institutions such as the Ombudsman in solving governmental (BUMN) problems regarding public service.